Exploring the relationship between vaccine hesitancy and mothers' perspectives on COVID-19 vaccines for children ages 5-11 years during the omicron predominant period 2021-2022: a qualitative study - Tiffany A. Suragh; David Adzrago; Marlyn A. Allicock; Paul G. Yeh; Paula Cuccaro (Frontiers Media S.A., 2024)
BackgroundThe United States Food and Drug Administration authorized COVID-19 vaccines for children ages 5-11 years in October 2021 during the Omicron predominant period. Parental vaccine hesitancy was prevalent during this time, resulting in low childhood COVID-19 vaccine uptake. Most studies exploring factors influencing parental vaccine hesitancy have focused on racial and ethnic minorities and lower socioeconomic populations; however, there is little knowledge of the drive drivers of vaccine hesitancy among White parents with higher education and socioeconomic statuses.MethodsWe conducted semi-structured interviews with a sample of 15 White mothers of children ages 5-11 years in Atlanta, GA, between October-December 2021. Thematic analysis was performed using NVivo 12.ResultsMothers were college-educated, homeowners, and fully vaccinated against COVID-19. Key findings included decreased pediatrician's recommendations for COVID-19 vaccines, reliance on information from specialized doctors and scientists, distrust in public health authorities, high risk-perception of COVID-19 vaccines, and low risk-perception of COVID-19 disease. Factors related to vaccine acceptance were altruism and practicality.ConclusionThis study adds to the sparse literature on reasons for vaccine hesitancy among White mothers of children ages 5-11 years with higher educational and socioeconomic status. Improving vaccine uptake among this group is critical for protecting the health of their children and other vulnerable populations. Tailored vaccine messaging and intervention are warranted to address their unique attitudes, beliefs, and behaviors. An enhanced understanding of the factors influencing subpopulations of parents can help vaccine policymakers and healthcare providers improve efforts to reduce vaccine hesitancy, particularly for new vaccines.